2016
DOI: 10.1155/2016/6521567
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between Subjective Sensations during First and Second Phacoemulsification Eye Surgeries in Patients with Bilateral Cataract

Abstract: Purpose. To evaluate and compare the subjective sensations reported by patients during first and second cataract extractions. Methods. Consecutive patients undergoing bilateral sequential cataract extraction using phacoemulsification were recruited. Following cataract surgery, patients completed questionnaires designed to evaluate subjective sensations, including anxiety, eye bulges, pain, and light sensitivity. Changes in painful sensations experienced by patients between the two surgeries were also recorded.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
32
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 25 publications
4
32
0
Order By: Relevance
“…We found a subtle, but statistically significant increase in pain in patients undergoing second eye surgery. This has previously been reported for various types of ophthalmic anesthesia [22][23][24][25][26][27] and is likely to be related to the lower preoperative anxiety prior to second eye surgery, 25,26 or amnestic effect of intravenous sedation. 26 In this study, sub-Tenon's anesthesia achieved great results with complete akinesia and we highlighted some advantages of this technique over cataract/refractive lens exchange performed with topical anesthesia only.…”
Section: Discussionsupporting
confidence: 55%
“…We found a subtle, but statistically significant increase in pain in patients undergoing second eye surgery. This has previously been reported for various types of ophthalmic anesthesia [22][23][24][25][26][27] and is likely to be related to the lower preoperative anxiety prior to second eye surgery, 25,26 or amnestic effect of intravenous sedation. 26 In this study, sub-Tenon's anesthesia achieved great results with complete akinesia and we highlighted some advantages of this technique over cataract/refractive lens exchange performed with topical anesthesia only.…”
Section: Discussionsupporting
confidence: 55%
“…A pain-related inflammatory chemokine was significantly increased in aqueous humor in the fellow eye after first-eye cataract surgery. This suggested there may be a sympathetic ophthalmic type uveitis in the contralateral eye after first-eye cataract surgery [ 21 ],[ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…These studies have suggested that patients undergoing their second-cataract surgery tend to experience less anxiety and greater pain than those undergoing their first-cataract surgery. 4,[10][11][12] There is, however, a lack of detailed knowledge about patients' subjective feelings just prior to cataract surgery. Accordingly, in this study, we aimed to investigate patient feedback related to various aspects of surgical preparation and the waiting period before cataract surgery depending on whether patients were undergoing their first-or secondcataract surgeries.…”
Section: Introductionmentioning
confidence: 99%